The Strategies For Increasing Palm Oil Productivity In Community Plantations In Tumbuk Village, Pagar Jati Sub-District, Central Bengkulu Regency - Shelli Ulandari; Ana Nurmalia; Evi Andriani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The province of Bengkulu has significant potential for the development of oil palm plantations. Tumbuk Village in Central Bengkulu Regency is an area with many community-owned oil palm plantations. Oil palm productivity in this village is still relatively low, so further research is needed. With a favourable climate and fertile soil, this area has the potential to increase oil palm productivity. The research aims to identify the internal and external factors that affect oil palm productivity in community plantations in Tumbuk Village and to determine the appropriate strategies for increasing oil palm productivity in community plantations in Tumbuk Village. The research method used was qualitative with a descriptive research type using SWOT (Strength, Weakness, Opportunity, Threat) analysis as well as IFAS and EFAS analysis methods. The results of the study on strategies to increase oil palm productivity in community plantations in Tumbuk Village, Pagar Jati Sub-District, Central Bengkulu Regency, revealed that the main strength factor was the high quality of seedlings (score of 0.53), the main weakness factor was the dense planting distance (score of 0.39), and the total weight score of the Internal Factor Evaluation Matrix was 2.87. The main opportunity factor is supportive government policies (score of 0.59), the main threat factor is the impact of pests and diseases (score of 0.27), and the total weight score of the External Factor Evaluation Matrix is 2.39. There are five (5) alternative strategies for increasing oil palm productivity in community plantations in Tumbuk Village, Pagar Jati Sub-District, Central Bengkulu Regency, namely: 1) Applying balanced and timely fertilization according to plant needs and soil conditions, 2) Using sufficient labor for routine maintenance and comprehensive land sanitation, 3) Performing intensive care of old plants with balanced fertilization and proper disease control, 4) Strengthening seed quality by selecting superior seeds and providing optimal care such as fertilization and routine pest control, 5) Performing balanced fertilization in a timely manner according to the plant's growth phase to optimize nutrient absorption.